2024
DOI: 10.3389/feduc.2024.1291669
|View full text |Cite
|
Sign up to set email alerts
|

Service-Learning as a niche innovation in higher education for sustainability

Alejandro Álvarez-Vanegas,
Shyama V. Ramani,
Louis Volante

Abstract: Education for Sustainable Development (ESD) is a framework proposed by UNESCO to develop knowledge, skills, values, and behaviors in youth for sustainable development. As part of the global development agenda, higher educational institutions are expected to integrate ESD into their curricula. Service-Learning is a type of experiential learning in which students combine academic coursework with community service which is aligned with the learning objectives of their academic program. In light of the global tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…SL focuses equally on the service being provided and the learning occurring (Bringle and Hatcher, 2000). It is considered an effective pedagogical approach vis-a-vis real-world transformations towards sustainability: it is action-oriented as it helps solve existing sustainability problems while it allows students to become more aware of unsustainable realities and more capable of examining them critically and actively tackling their causes (Álvarez-Vanegas et al, 2024). This is aligned with the perspective of Deeley (2016), who posits that the main effects identified in the literature of SL can be categorised into three groups:…”
Section: Competences and Actionmentioning
confidence: 99%
“…SL focuses equally on the service being provided and the learning occurring (Bringle and Hatcher, 2000). It is considered an effective pedagogical approach vis-a-vis real-world transformations towards sustainability: it is action-oriented as it helps solve existing sustainability problems while it allows students to become more aware of unsustainable realities and more capable of examining them critically and actively tackling their causes (Álvarez-Vanegas et al, 2024). This is aligned with the perspective of Deeley (2016), who posits that the main effects identified in the literature of SL can be categorised into three groups:…”
Section: Competences and Actionmentioning
confidence: 99%
“…So far, only two SLR-based articles have been found that are related to higher education, i.e. about service-learning as a niche innovation for sustainability (A Álvarez-Vanegas et al, 2024) and connecting competencies and pedagogical approaches (Lozano et al, 2017). Thus, it can be said that no SLR has been found that focuses on SC and university.…”
Section: Introductionmentioning
confidence: 99%